The Accuracy of Earning Forecast Analysis, Information Asymmetry and Integrated Reporting – Case of Indonesia - Novita Indrawati (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
The purpose of this study is to examine factors that affect companies presents the elements of integrated reporting in their annual reports and how its effect on the accuracy of earnings forecast analysis and information asymmetry. The independent variables tested were institutional ownership, company size, profitability, international activities, and industry type and growth opportunity. The study population is non-financial companies listed on the Indonesia Stock Exchange in 2015. The samples were taken by using purposive sampling i.e. with some specific criteria. The data was analysed by using multiple regression analysis to examine the factors affecting the company presents the elements of integrated reporting in the annual report, and a simple regression to see how the presentation of the elements of integrated reporting affect the asymmetry of information and the accuracy of earnings forecast analysis. This study found that only the size of the companies determines the presentation of the elements ofintegrated reporting in the annual report. In addition, this study does not confirm the effect of the presentation of the elements of integrated reporting on the information asymmetry and the earnings forecast analysis accuracy.